An Alternative for Short Renal Vein During Kidney Transplantation: Long-term Experience With Polyethylene Terephthalate (Dacron) Vascular Graft - TİNAY, İLKER; TUĞLULAR, ZÜBEYDE SERHAN (ELSEVIER SCIENCE INC, 2013)
OBJECTIVE To describe the first long-term experience with the polyethylene perephthalate vascular graft to lengthen a short renal vein during kidney transplantation. MATERIALS AND METHODS The polyethylene terephthalate vascular graft was interposed between the short renal vein of the donor kidney and the recipient's external iliac vein using 6-0 Prolene suture on a 13-mm needle. The postoperative follow-up protocol of the patients included regular serum creatinine levels and Doppler ultrasound scans. RESULTS The median follow-up period was 74.5 months (range 51-128). Postoperative Doppler ultrasonography showed no complications in any of the patients. None of our patients experienced any kind of rejection. The median creatinine level at the last follow-up visit was 0.99 mg/dL (range 0.73-1.56). CONCLUSION In our experience, the use of polyethylene terephthalate vascular grafts as a venous graft for the short renal vein in kidney transplantation provides an alternative option with long-term success. UROLOGY 82: 245-247, 2013. (C) 2013 Elsevier Inc.